Acute malnutrition relapse and associated factors among 6–59 months old children treated in the community-based management of acute malnutrition in Dessie, Kombolcha, and Haik towns, Northeast Ethiopia - Yitayew, Yibeltal Asmamaw; Yalew, Zemen Mengesha; Nebiyu, Samuel; Jember, Desalegn Abebaw (Frontiers in Public Health, 2024)
Introduction Undernutrition is a major health concern in many developing countries, and is one of the main health problems affecting children in Ethiopia. Although many children experience multiple relapses following the management of severe acute malnutrition, it is scarcely studied in Ethiopia. Methods A community-based cross-sectional study was conducted in Dessie, Kombolcha, and Haik towns among 6-59-month-old children enrolled and discharged from community-based acute malnutrition management (CMAM). The total sample size was 318 children, and data were collected from April 15, 2021, to May 14, 2021. The data were entered into EPI data version 4.4.1 before being exported and analyzed with SPSS version 25 software. A multivariate logistic regression analysis was performed, and a 95% confidence interval and p-value <0.05 were used to identify significantly associated variables. Additionally, the weight-for-height z-score (WHZ) was generated using the WHO Anthro 3.2.2 software. Result The overall acute malnutrition relapse after discharge from CMAM was 35.2% (6.6% relapsed to severe acute malnutrition and 28.6% relapsed to moderate acute malnutrition). The following variables were significantly associated with the relapse of acute malnutrition: child age (AOR: 3.08, 95% CI; 1.76, 5.39), diarrhea after discharge (AOR: 2.93, 95%CI; 1.51, 5.69), have not immunized (AOR: 3.05, 95% CI; 1.14, 8.23), MUAC at discharge (AOR: 3.16, 95% CI; 1.56, 6.40), and poorest and poor wealth index (AOR: 3.65, 95% CI; 1.45, 9.18) and (AOR: 2.73, 95% CI; 1.13, 6.59), respectively. Conclusion Over one-third of children treated with the CMAM program reverted to SAM or MAM. The age of the child, diarrhea after discharge, lack of immunization, MUAC at discharge (<13 cm), and poor and poorest wealth index were significantly associated with acute malnutrition relapse. Therefore, adequate health education and counseling services are essential for mothers to improve child immunization coverage and maintain adequate hygiene to prevent diarrhea. In addition, further experimental research is needed to investigate the effect of MUAC at discharge on the risk of acute malnutrition relapse.